2014
DOI: 10.3758/s13414-014-0769-1
|View full text |Cite
|
Sign up to set email alerts
|

A decisional account of subjective inflation of visual perception at the periphery

Abstract: Human peripheral vision appears vivid compared to foveal vision; the subjectively perceived level of detail does not seem to drop abruptly with eccentricity. This compelling impression contrasts with the fact that spatial resolution is substantially lower at the periphery. A similar phenomenon occurs in visual attention, in which subjects usually overestimate their perceptual capacity in the unattended periphery. We have previously shown that at identical eccentricity, low spatial attention is associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
94
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(102 citation statements)
references
References 63 publications
8
94
0
Order By: Relevance
“…Such an attentional bias would enhance perception in everyday life, as we are inclined to foveate behaviorally relevant objects even though we might not be consciously aware of our limited perceptual abilities peripherally. Indeed, subjects tend to overestimate their peripheral performance (Solovey et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Such an attentional bias would enhance perception in everyday life, as we are inclined to foveate behaviorally relevant objects even though we might not be consciously aware of our limited perceptual abilities peripherally. Indeed, subjects tend to overestimate their peripheral performance (Solovey et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, criteria could also reflect differences in perception itself, including perceptual shifts driven by visual illusions (Witt et al , 2015). Likewise, another study observed liberal criteria for detection in the peripheral vision, and the authors argued that this reflects the inflated subjective sense of perception in the periphery (Solovey et al , 2015). Perhaps the current results likewise reflect biases at the perceptual level.…”
Section: Discussionmentioning
confidence: 98%
“…To address the question of whether liberal detection biases are evident when making judgments in the unattended periphery, we conducted a study where subjects engaged in a naturalistic task of simulated driving while they looked for (i.e., detected) specific colors of pedestrians' clothing in the visual periphery. Unlike in previous studies (Rahnev, Maniscalco, et al, 2011;Solovey et al, 2015), the stimuli were not degraded by noise or reduced contrast; instead, near-threshold task difficulty was created more naturalistically by having the pedestrians move at a fast speed. We reasoned that if the previous results (Rahnev, Maniscalco, et al, 2011;Solovey et al, 2015) were not due to idiosyncratic strategies adopted in artificial psychophysics experiments, here, subjects should exhibit similar liberal detection biases in the unattended periphery as well.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has addressed this question within the framework of Signal Detection Theory. Results show that observers tend to use liberal detection biases when evaluating peripheral or unattended stimuli, such as grating patterns embedded in noise (Rahnev, Maniscalco, et al, 2011;Solovey, Graney, & Lau, 2015); that is, participants were more likely to say that items were presented in peripheral or unattended locations, even when they were not. These results were interpreted to reflect a subjective sense of inflated phenomenology in the unattended periphery, because detection biases could in principle reflect both subjective perception and decisional or response strategies (Witt, Taylor, Sugovic, & Wixted, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation